2017
DOI: 10.1111/1365-2656.12766
|View full text |Cite|
|
Sign up to set email alerts
|

Migratory animals feel the cost of getting sick: A meta‐analysis across species

Abstract: Abstract1. Migratory animals are widely assumed to play an important role in the long-distance dispersal of parasites, and are frequently implicated in the global spread of zoonotic pathogens such as avian influenzas in birds and Ebola viruses in bats.However, infection imposes physiological and behavioural constraints on hosts that may act to curtail parasite dispersal via changes to migratory timing ("migratory separation") and survival ("migratory culling").2. There remains little consensus regarding the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
60
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 87 publications
1
60
1
Order By: Relevance
“…We fit the REMs with restricted maximum likelihood (REML) to obtain unbiased estimates of variance components, from which we calculated I 2 to quantify the contribution of true heterogeneity to total variance in effect size (Nakagawa & Santos 2012;Senior et al 2016). We repeated analyses on observational data divided by intensity (n = 359) and infection status (n = 143) to account for differences in the condition-infection relationship that could arise from how parasitism was measured (Risely et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We fit the REMs with restricted maximum likelihood (REML) to obtain unbiased estimates of variance components, from which we calculated I 2 to quantify the contribution of true heterogeneity to total variance in effect size (Nakagawa & Santos 2012;Senior et al 2016). We repeated analyses on observational data divided by intensity (n = 359) and infection status (n = 143) to account for differences in the condition-infection relationship that could arise from how parasitism was measured (Risely et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Infections are known to hamper migration performance in a variety of taxa, including mammals (Mysterud et al 2016), insects (Bradley and Altizer 2005), fish (Sjöberg et al 2009) and birds (Risely et al 2018) and we recently demonstrated that an energetically costly mimicked bacterial infection increases stopover duration in songbirds (Hegemann et al 2018). However, there is no study investigating to what extent mild and/or chronic parasite infections impact stopover ecology in songbirds, which constitute the vast majority of avian migrants.…”
Section: Introductionmentioning
confidence: 92%
“…Together with findings that individuals carrying infections can show poorer physical endurance (Bradley & Altizer, ), slower migration (Bradley & Altizer, ; van Gils et al., ) and move shorter distances (Sjöberg et al., ), this opens up the possibility that immune responses during migration form a major physiological mechanism for carry‐over effects between annual‐cycle stages (Studds & Marra, ). Effects of infections on migration have also been associated with lower rates of survival (Risely et al., ). Hence, this mechanism could also support the idea of migratory culling, that is selective removal of infected hosts during demanding migration journeys (Bradley & Altizer, ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it has been hypothesized that trade‐offs between immune function and refuelling rate exist, and this would increase stopover duration and hence reduce migration speed (Klaassen, Hoye, Nolet, & Buttemer, ). Indeed, observational studies suggest that pathogens can impair migration in insects (Bradley & Altizer, ), fish (Sjöberg, Petersson, Wickstrom, & Hansson, ) and birds (van Gils et al., ), and a recent meta‐analysis across taxa indicates that parasites and infection intensity negatively impact migration performance (Risely, Klaassen, & Hoye, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation